1999
DOI: 10.1007/s004390050925
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure, promoter characterisation and mutational analysis of the S100A7 gene: exclusion of a candidate for familial psoriasis susceptibility

Abstract: We have recently assigned a locus for familial psoriasis (PS) susceptibility to the region containing the epidermal differentiation complex gene cluster on chromosome 1q21. Gene S10OA7 maps within this cluster and is reported to be markedly over-expressed in the skin lesions of psoriatic patients. In order to analyse S100A7 as a candidate for PS susceptibility, we have determined its genomic structure regarding exon-intron boundaries and the transcription start site. The gene is organised in three exons and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 20 publications
0
30
1
2
Order By: Relevance
“…S100A7 was originally identified as a protein whose expression was increased in psoriatic keratinocytes 9. Later studies have shown that S100A7 could play an important role in antibacterial action10 and its overexpression is prominently associated with early stages of various carcinomas, including squamous carcinomas in skin and bladder, and ductal in situ carcinomas and adenocarcinomas of the breast 11 – 16. Expression of S100A7 is often diminished in carcinomas during their progression to invasive carcinoma.…”
mentioning
confidence: 99%
“…S100A7 was originally identified as a protein whose expression was increased in psoriatic keratinocytes 9. Later studies have shown that S100A7 could play an important role in antibacterial action10 and its overexpression is prominently associated with early stages of various carcinomas, including squamous carcinomas in skin and bladder, and ductal in situ carcinomas and adenocarcinomas of the breast 11 – 16. Expression of S100A7 is often diminished in carcinomas during their progression to invasive carcinoma.…”
mentioning
confidence: 99%
“…К сожалению, некоторые из этих маркёров, такие как протеины S100 А7, А8 и А9, экспрессируются не только при псори-азе [25,33], но также в случае других воспали-тельных кожных заболеваний [16,29]. В работах M. Nold и соавт.…”
Section: современные представления об этиопатогенезе псориаза и псориunclassified
“…(2013) показана увеличенная экс-прессия IL-36γ в коже у пациентов с псориазом (n=38 и n=17) [20]. В отличие от других маркё-ров, описанных раннее при псориазе, например S100 А7, А8 и А9 [16,23,25,33], маркёр IL-36γ ока-зался высокоспецифичным для псориаза (при других воспалительных заболеваниях кожи, в том числе атопическом дерматите и контактной экземе, экспрессия выражена слабо) [20].…”
Section: роль Il-36γ в воспалительных заболеваниях кожиunclassified
“…The EDC includes members of S100 and small proline-rich region (SPRR) gene clusters and cornified envelope genes known to be structurally related to SPRR or S100 genes, including filaggrin, trichohyalin, loricrin and involucrin. Among these genes, loricrin[26], S100A2 [27] and S100A7 [28] are excluded as candidates for the PSORS4 locus. A recent study revealed that the association of psoriasis to the PGLYRP and SPRR genes at the PSORS4 locus on 1q21 shows heterogeneity among Finnish, Swedish and Irish families [29].…”
Section: Discussionmentioning
confidence: 99%